Permisos transables frente a la introducción de un combustible limpio: estudio de caso para PM-10 y NOx en Santiago, Chile - O'Ryan, Raul; Bravo, Rodrigo (Estudios de Economía, 2016)
Beginning in 1990 a compensation system for PM-10 emissions from pointsources was implemented in Santiago, equivalent to a suboptimal emission permitsystem (EPS). The objective of the system was to reduce compliance costs andto prevent emissions from new sources, forcing them to compensate all emissionswith existing sources. The system basically did not operate until 1997, year inwhich natural gas –a clean fuel– was introduced into Santiago. In this context,this paper examines the following questions: What is the impact of theintroduction of natural gas in the applicability of tradeable permits for PM-10and NOx? Are they justified or are the efficiency gains so small that directregulation is preferable? The efficiency gains associated to an optimal ambientpermit system (APS) are quantified and compared to the simpler EPS. Finallycontrol cost functions are developed for Santiago for fixed point sources andpresented in detail.